Job empowerment requirements for administrators in Iraqi sports clubs - Hassoun, Hussein Karim (Jurnal Ilmu Keolahragaan, 2025)
Background. Sports clubs are one of the vital institutions that play a pivotal role in the development and development of the sports sector, as the quality of their administrative and organizational performance depends largely on the efficiency of the administrators working in it, and in the Iraqi context, sports clubs face increasing challenges related to environmental, economic and organizational changes. Objectives. This research aims to identify the requirements for the functional empowerment of Administrators in Iraqi sports clubs. Methods The researchers used a descriptive approach (survey study), which provides an understanding of the requirements for the functional empowerment of administrators in Iraqi sports clubs. The research sample included 121 administrators working in 22 sports clubs in 6 provinces of Iraq. The instrument used was a questionnaire as the main data collection tool. After completing the questionnaire administration, the data were collected, classified, analyzed, and tabulated to perform appropriate statistical analysis. Results. the results also showed that functional empowerment is based on the principle of mutual trust between management Finally, administrators in Iraqi sports clubs need full authorization in making decisions related to club management, the researcher also recommended the need to provide specialized training programs for administrators in Iraqi sports clubs, in order to enhance their skills in sports management and strategic planning, while working on adopting a policy of full authorization in decision-making by senior management, to provide an enabling environment that enhances the ability of administrators to respond quickly to changes and achieve goals. Conclusion. Career empowerment is based on the principle of mutual trust between senior management and administrators. Career empowerment pushes managers to deliver professional and constantly evolving performance. Administrators in Iraqi sports clubs need full authorization in making decisions related to the management of the club.